THE HEMATOLOGICAL EFFECT OF SALMONELLA TYPHIMURIUM ENDOTOXIN IN RABBITS - Khalil H.Z. Al-Joboury; Mohammed A.Y.Al-Amery Faisal G.Habasha (Basrah Journal of Veterinary Research)
End toxin is responsible for different changes in body systems. This study was conducted to study hematological changes by using 20 rabbits, were randomly divided into 4 equal groups, then gave intravenous endotoxin doses 5, 15 and 20 µg/Kg body weight for groups I, II and III respectively, while group IV gave PBS as a control. The hematological findings included marked leukopenia due to neutropenia followed by marked leukocytosis with left shift associated with lymphocytosis, monocytosis and basophilia. Total erythrocytes, packed cell volume and hemoglobin concentration were increased during first hour, while the following time showed gradual decrease to develop anemia, which manifested by macrocytic hypochromic, in relation to the increased mean corpuscular volume and decreased mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration. Also thrombocytopenia, while the total plasma protein and fibrinogen showed pronounced increased due to endotoxemia